Effect of MOOC Learning Duration on Achievement of Learning Goals - Miftachul Amri; Zhang Wei; Arthur Hajar Hantoro; Rudiansyah Rudiansyah; Khairunnisa Khairunnisa (Journal of Social Science Utilizing Technology, 2024)
Background. Education in the 21st century has experienced significant changes with the development of digital technology. The use of media and technology in the learning process is becoming increasingly important to meet the demands of the times. One of the innovations that has emerged is the Massive Open Online Course (MOOC), an online learning platform that provides open access to learning materials from various fields globally. MOOCs promise great flexibility and accessibility, which can increase participation in education. Purpose. This research aims to investigate the effect of MOOC learning duration on the achievement of educational students’ learning objectives. Method. The research method used is a quantitative approach with survey methods. A total of 30 education student respondents who had taken MOOC courses were the research subjects. Data was collected by filling out a questionnaire distributed via the WhatsApp group. Data analysis was carried out using the Miles Huberman technique to investigate the relationship between MOOC learning duration and achievement of learning objectives. Results. The research results showed that the majority of participants felt that the MOOC learning duration provided benefits in understanding the learning material and increasing their learning motivation. However, some participants felt neutral regarding the contribution of learning duration in completing assignments and exams. The majority of respondents did not feel a significant impact of longer duration on achieving higher learning goals.   Conclusion. Although MOOC learning duration provides benefits in understanding the material and learning motivation, there are several aspects that need to be considered. The role of other factors such as the quality of learning materials and interaction between participants and instructors may be more important in achieving learning objectives. Therefore, course organizers need to continue to monitor participant feedback and evaluate the learning duration offered to improve the learning experience in MOOCs.